2018
DOI: 10.1159/000487811
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Improved Dysphagia Care on Outcome in Patients with Acute Stroke: Trends from 8-Year Data of a Large Stroke Register

Abstract: Background: Early dysphagia screening and appropriate management are recommended by current guidelines to reduce complications and case fatality in acute stroke. However, data on the potential benefit of changes in dysphagia care on patient outcome are limited. Our objective was to assess the degree of implementation of dysphagia guidelines and determine the impact of modifications in dysphagia screening and treatment practices on disease complications and outcome in stroke patients over time. Methods: In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
1
14
1
1
Order By: Relevance
“…Comparison of patient groups, that is, with vs. without dysphagia, in our study confirms previously shown higher complication rate and worse outcome in dysphagic individuals [6] including higher need for artificial ventilation, incidence of pulmonary infection and longer LOS in affected patients, indicating once again the relevance of timely identification of dysphagia. Interestingly the overall mortality did not differ significantly.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Comparison of patient groups, that is, with vs. without dysphagia, in our study confirms previously shown higher complication rate and worse outcome in dysphagic individuals [6] including higher need for artificial ventilation, incidence of pulmonary infection and longer LOS in affected patients, indicating once again the relevance of timely identification of dysphagia. Interestingly the overall mortality did not differ significantly.…”
Section: Discussionsupporting
confidence: 89%
“…It can lead to malnutrition and dehydration, and importantly, is associated with a worse long-term outcome including prolonged hospitalisation and extensive care dependency [1][2][3][4]. Especially the occurrence of aspiration pneumonia as typical and partly avoidable complication of swallowing disorders increases the overall mortality of stroke patients [5,6]. Pneumonia incidence has been shown to increase 1% per day of delay in dysphagia screening [7].…”
Section: Introductionmentioning
confidence: 99%
“…In this clinical scenario, an accurate swallowing screening test may be crucial in lowering the incidence of SAP. Indeed, recent studies reported a higher SAP incidence in stroke patients who failed a high-sensitive screening for dysphagia compared to those who passed the screening [12,13]. In this view, measuring patients' pulse oximetry and laryngeal elevation could improve the accuracy of dysphagia bedside assessment [14][15][16][17][18], being important in detecting aspiration and consequently in reducing dysphagia-related pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Oropharyngeal dysphagia frequently occurs in several neurological disorders such as stroke 1 , Parkinson's disease 2 , dementia 3,4 , multiple sclerosis 5 or neuromuscular disorders such as inflammatory myopathies or myasthenia gravis [6][7][8] , but also as age-related dysphagia in elderly otherwise healthy people 9 . Dysphagia not only affects patients' quality of life 10 , but is also prone to severe complications such as malnutrition, dehydration and aspiration pneumonia resulting in worse long-term outcome and increased mortality 1,8,[11][12][13][14][15][16][17][18][19][20] . In fact, pneumonia after aspiration is often a leading cause of death in these patient groups 1,8,18,[20][21][22][23] .…”
mentioning
confidence: 99%